The Handicraft Training for Diffability by KKN UNS in Comoro, Timor Leste - Gama Hatta Novika, Revi; Sayful Zuhri, Moh; Noronha Martins, Pascoela; Baptista Barros, Odete; Cipriana de Araujo Liberata, Melania; F. A. P. Gonçalves, Julia; I. da Silva Castanheira, Odelia; de Araujo Fernandes, Antonio (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The university has the tri dharma of higher education, one of which is community service. Community service programs for students can be carried out by taking real work courses (KKN). In KKN activities, students are required to have a work program that is tailored to the needs of the community at the KKN location. The implementation of KKN in addition to Indonesia is also carried out in Timor Leste which is carried out by UNS foreign students. After the survey was carried out, KKN students carried out a program intended for persons with disabilities. This program is motivated by the problems faced so that people with disabilities have independence through the program to be implemented. People with disabilities are often underestimated and have stereotypes from society because of their physical limitations. Students carry out handicraft training programs for people with disabilities. This is so that people with disabilities can optimize and improve their abilities. In addition to handicraft training, other supporting programs are also implemented, such as educational activities, entrepreneurship and many more. This is done so that people with disabilities can live independently in the future. This program has quite a good impact for people with disabilities because there is encouragement from KKN students. And have confidence in their work.